Calculations of Electric Fields of Circular Screened Systems, Generated from Cylindrical Piezoceramic Radiators - LEIKO, Aleksandr; DEREPA, Anatolii; RASSTRYGIN, Aleksandr; KOSIAKOVSKYI, Andrii; KOCHARIAN, Oksana; STAROVOIT, Yaroslav (Archives of Acoustics, 2019)
Analytical relations, describing the electrical fields of cylindrical piezoceramic radiators with circular polarization as a member of the cylindrical systems with the baffle in the inner cavity, using the related fields method in multiply connected regions were obtained. Comparative analysis of the results of numerical experiments performed on the frequency characteristics of the electric field of the radiating systems for different modes of radiation allow to establish a number of subtle effects of the formation of the electric field of radiators.